SITUS BACUKIKI DI KOTA PARE-PARE: PELUANG PEMANFAATAN SEBAGAI OBJEK WISATA BUDAYA - nfn Muhaeminah (Balai Arkeologi Provinsi Sulawesi Selatan, 2010)
The history revealed that The Kingdom of Bacukiki, Parepare (now is a part of South Sulawesi was visited by Portuguese ships around XVI century in the same period with Suppa, Alitta, Sidenreng and Siang Kingdom. Nowadays, the ex-river harbour called